2012
DOI: 10.1007/s10875-012-9702-3
|View full text |Cite
|
Sign up to set email alerts
|

Selective IgA Deficiency: Clinical and Laboratory Features of 118 Children in Turkey

Abstract: Selective IgA deficiency (IgAD) is considered as the most common primary immunodeficiency. Although the vast majority of affected individuals are asymptomatic, symptomatic patients suffer from recurrent infections, allergies and autoimmune diseases. In the present study, we aimed to investigate the clinical and laboratory features of children with IgAD in a tertiary children's hospital in Turkey. The medical records of 118 patients (63 males, 55 females) aged 4-18 years (median: 7 years) seen from 2006 to 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 37 publications
3
58
2
1
Order By: Relevance
“…In our stud, all IgA-deficient children manifested cutaneous symptoms of food allergy and while atopic dermatitis occurred in patients with all kinds of hypogammaglobulinemia, solely in IgA-deficient children studied; the correlation between symptoms and immunodeficiency was statistically significant. This finding is consistent with observations also made by other authors who reported an association of impaired antibody production with atopic dermatitis in children [6,18], and which was also found in our previous study [19]. Interestingly, it has been shown recently that cutaneous sensitization may predispose patients to an intestinal allergy by the increased production of thymic stromal lymphopoietin (TSLP) and subsequent T-helper type 2 (Th2)-dependent immune responses to food antigens in the skin [20,21].…”
Section: Discussionsupporting
confidence: 94%
“…In our stud, all IgA-deficient children manifested cutaneous symptoms of food allergy and while atopic dermatitis occurred in patients with all kinds of hypogammaglobulinemia, solely in IgA-deficient children studied; the correlation between symptoms and immunodeficiency was statistically significant. This finding is consistent with observations also made by other authors who reported an association of impaired antibody production with atopic dermatitis in children [6,18], and which was also found in our previous study [19]. Interestingly, it has been shown recently that cutaneous sensitization may predispose patients to an intestinal allergy by the increased production of thymic stromal lymphopoietin (TSLP) and subsequent T-helper type 2 (Th2)-dependent immune responses to food antigens in the skin [20,21].…”
Section: Discussionsupporting
confidence: 94%
“…However, different studies report different prevalences of autoimmunity in sIgAD. While Shkalim et al [107] reported that 20.6% of IgAD children in Israel showed manifestations of autoimmunity, Edwards et al [108] reported 28%, Aytekin et al [109] reported 17%, and more recently Abolhassani et al [8] reported 29.8%. In this study the most common autoimmune manifestations were thyroiditis, vitiligo, and AIHA, followed by celiac disease, juvenile rheumatoid arthritis, dermatomyositis, autoimmune alopecia, and T1D.…”
Section: Autoimmunity In Padsmentioning
confidence: 99%
“…Most affected individuals are asymptomatic, whereas approximately one third of patients suffer from recurrent mucosal infections, allergies, and autoimmune diseases (2)(3)(4). Secretory IgA, which is present in mucosal secretions, has a broad protective function, and in the case of sIgAD the mucosa appears to be less protected and more vulnerable to enteric toxins and pathogenic microorganisms (5).…”
Section: Introductionmentioning
confidence: 99%